Effect of pancreas disease vaccines on infection levels and virus transmission in Atlantic salmon (Salmo salar) challenged with salmonid alphavirus, genotype 2 - Thorarinsson, Ragnar; Ramstad, Anne; Wolf, Jeffrey C.; Sindre, Hilde; Skjerve, Eystein; Rimstad, Espen; Evensen, Øystein; Rodriguez, Jose F. (Frontiers in Immunology, 2024)
Salmonid alphavirus (SAV) causes pancreas disease (PD), which negatively impacts farmed Atlantic salmon. In this study, fish were vaccinated with a DNA-PD vaccine (DNA-PD) and an oil-adjuvanted, inactivated whole virus PD vaccine (Oil-PD). Controls were two non-PD vaccinated groups. Fish were kept in one tank and challenged by cohabitation with SAV genotype 2 in seawater. Protection against infection and mortality was assessed for 84 days (Efficacy study). Nineteen days post challenge (dpc), subgroups of fish from all treatment groups were transferred to separate tanks and cohabited with naïve fish (Transmission study 1) or fish vaccinated with a homologous vaccine (Transmission study 2), to evaluate virus transmission for 26 days (47 dpc). Viremia, heart RT-qPCR and histopathological scoring of key organs affected by PD were used to measure infection levels. RT-droplet digital PCR quantified shedding of SAV into water for transmission studies. The Efficacy study showed that PD associated growth-loss was significantly lower and clearance of SAV2 RNA significantly higher in the PD-DNA group compared to the other groups. The PD-DNA group had milder lesions in the heart and muscle. Cumulative mortality post challenge was low and not different between groups, but the DNA-PD group had delayed time-to-death. In Transmission study 1, the lowest water levels of SAV RNA were measured in the tanks containing the DNA-PD group at 21 and 34 dpc. Despite this, and irrespective of the treatment group, SAV2 was effectively transmitted to the naïve fish during 26-day cohabitation. At 47 dpc, the SAV RNA concentrations in the water were lower in all tanks compared to 34 dpc. In Transmission study 2, none of the DNA-PD immunized cohabitants residing with DNA-PD-vaccinated, pre-challenged fish got infected. In contrast, Oil-PD immunized cohabitants residing with Oil-PD-vaccinated, pre-challenged fish, showed infection levels similar to the naïve cohabitants in Transmission study 1. The results demonstrate that the DNA-PD vaccine may curb the spread of SAV infection as the DNA-PD vaccinated, SAV2 exposed fish, did not spread the infection to cohabiting DNA-PD vaccinated fish. This signifies that herd immunity may be achieved by the DNA-PD vaccine, a valuable tool to control the PD epizootic in farmed Atlantic salmon.